Study of Socio Economic and Annual Income Status of Haibatpur Village: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Socio-economic survey is a very development activity. In socio-economic we prepare demographic details. Household category wise, population report, education status, land holding and cropping pattern of the village, lives stock details of the village. Annual income and expenditure of families in the village information is collected and analysis the changes that take place in the entire village as well as in each individual family.